Život na pevnině. - Sinice a řasy - Elster, J. (Josef); Komárek, J. (Jiří); Nedbalová, L. (Linda) (2013)
Description of main habitats of cyanobacteria and algae in cryoseston and in deglaciated parts of the coastal Antarctica.